2017
DOI: 10.1002/dta.2167
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characterization and pharmacological evaluation of the new psychoactive substance 4‐fluoromethylphenidate (4F‐MPH) and differentiation between the (±)‐threo and (±)‐erythro diastereomers

Abstract: Misuse of (±)-threo-methylphenidate (methyl-2-phenyl-2-(piperidin-2-yl)acetate; Ritalin®, MPH) has long been acknowledged, but the appearance of MPH analogs in the form of ‘research chemicals’ has only emerged in more recent years. 4-Fluoromethylphenidate (4F-MPH) is one of these recent examples and this study presents the identification and analytical characterization of two powdered 4F-MPH products that were obtained from an online vendor in 2015. Interestingly, the products appeared to have originated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[11,13] Since methylphenidate is a widely regulated medicine, structurally diverse and often more potent NPS of the phenidate class have entered the drug market. [14,15] Molecular structures and the respective activities at DAT have been reported for many of these compounds in the scientific literature, making the targeted synthesis of potent phenidate analogues for the drug market likely. [16] Phenidates were recently seized by German authorities, such as 4methylmethylphenidate (2), 3,4-dichloromethylphenidate (3), ethylphenidate (4), 3,4-dichloroethylphenidate (5), and N-benzylethylphenidate (7), whereas ethylnaphthidate (6) was obtained from an Internet retailer ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,13] Since methylphenidate is a widely regulated medicine, structurally diverse and often more potent NPS of the phenidate class have entered the drug market. [14,15] Molecular structures and the respective activities at DAT have been reported for many of these compounds in the scientific literature, making the targeted synthesis of potent phenidate analogues for the drug market likely. [16] Phenidates were recently seized by German authorities, such as 4methylmethylphenidate (2), 3,4-dichloromethylphenidate (3), ethylphenidate (4), 3,4-dichloroethylphenidate (5), and N-benzylethylphenidate (7), whereas ethylnaphthidate (6) was obtained from an Internet retailer ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Numbers in parentheses correspond to the values for the known parent methyl-ester compounds. [15,25] effect rather than its chemical structure. [27] Procedure (1) can be difficult to implement and pharmaceutical legislation in, for example, Germany is not applicable to 'substances that […] are only consumed to intoxicate while being detrimental to health' according to a recent ruling by the European Court of Justice (ECJ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was revealed that one powdered product consisted of a diastereomeric mixture represented by racemic (±)‐ threo and (±)‐ erythro 4F‐MPH whereas the other product consisted of (±)‐ threo ‐4F‐MPH only, thus, reflecting distinct batches prepared during synthesis and incomplete product clean‐up. Furthermore, after chromatographic separation, both forms were subjected to in vitro pharmacological characterization using rat brain synaptosomes, which revealed that the biological activity, i.e., catecholamine selective blockade of monoamine reuptake, was associated with (±)‐ threo form …”
Section: The Presence Of Isomers When Identifying New Psychoactive Sumentioning
confidence: 99%
“…MPH is rapidly absorbed and hydrolyzed by carboxylesterase 1 liver enzymes to the inactive metabolite ritalinic acid (RA), which is excreted primarily in urine . Because MPH is a widely regulated medicine, several closely related unregulated substances, which are often more potent, have been launched on the NPS market . Multiple cases of misuse of phenidate analogues have been observed among recreational drug users, presumably due to their psychostimulant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific articles have been published in recent years regarding analytical characterization of phenidate analogues by nuclear magnetic resonance (NMR), infrared (IR) spectroscopy, gas chromatography‐mass spectrometry (GC‐MS), and liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC‐ESI‐MS/MS) . The confirmation of such chemical identities by MS techniques represents a challenging task because these analogues present information‐poor mass spectra in LC‐ESI‐MS/MS and in GC‐EI‐MS analysis, with a fragment/product ion representing mainly or only the secondary amine‐containing residue.…”
Section: Introductionmentioning
confidence: 99%